Hitler and the occult - Anderson, Ken (Prometheus Books, 1995)
Did the Holy Lance, which is said to have pierced the side of Jesus Christ, take center stage in Hitler's life as the focal point of his ambitions to conquer the world? Was there some mystical meaning behind Rudolf Hess's flight to Britain, Hitler's "extrasensory" perception, the Nazi swastika, the "superman" who haunted the Fuhrer, the use of Nostradamus in propaganda, and the Nazi astrological propaganda war? Anderson examines Hitler's alleged ties to the occult.
Keywords: Hitler, Adolf <1889-1945>; Hitler, Adolf -- 1889-1945; Nationaal-socialisme; Occultisme; Nationalsozialismus; National socialism and occultism; Occultism -- Germany; Okkultismus; Deutschland